Aging and Systemic Lupus Erythematosus - Immunosenescence and Beyond - Laurens van den Hoogen, Lucas; Patrick Sims, Gary; Adrianus Gijsbert van Roon, Joel; Dorothea Elisabeth Fritsch-Stork, Ruth (Current Aging Science, 2015)
The lifespan of humans has increased drastically over the last decades; considerable effort has been applied to delineate the mechanisms behind aging in order to find strategies for longevity. As the benefits of the gained knowledge might extend to diseases, where accelerated aging is suspected, the role of aging in the systemic autoimmune disease Systemic Lupus Erythematosus (SLE) is of particular interest. In this review the immunological similarities of SLE and aging are analyzed on three levels: the clinical, the cellular and the molecular, in order to find possible common pathological mechanisms. Common clinical features (e.g. increased infection rates, incidence of tumors and cardiovascular diseases) of SLE-patients and elderly individuals and shared characteristics of immuno-senescence and SLE are identified. These similarities are strongest in the adaptive immune system, where terminally differentiated T-cells and an immunological risk profile are found in both conditions. Also the aging innate immune system has overlapping features with SLE, exemplified by a generally lowered phagocytic capacity. However, great disparities between the aging immune system and SLE become apparent on a closer look, affecting numbers, phenotype and function of most immune cells, ranging from NETosis by granulocytes to the mechanisms underlying abnormal IL-2 production by T-cells. On the molecular level, also the increased presence of aging mechanisms like telomere attrition, DNA damage, autophagy and the characteristics of the mTOR pathway in SLE, possibly contributing to the shared changes on the cellular and clinical level are elaborated. The possible implications thereof concern existing (hydroxychloroquine, rapamycine, Glucocorticoids) as well as novel therapeutic strategies targeting more specific pathways which might rapidly reach the clinical arena. Overall a differential view on the similarities of aging and SLE and possible consequences is presented.
Keywords: lymphocytes